2013
DOI: 10.1155/2013/972601
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Extracorporeal Shock Wave Therapy for the Treatment of Chronic Pelvic Pain Syndrome: A Randomized, Controlled Trial

Abstract: Objectives. To investigate the effectiveness of extracorporeal shock wave therapy (ESWT) for symptoms alleviation in chronic pelvic pain syndrome (CPPS). Materials and Methods. 40 patients with CPPS were randomly allocated into either the treatment or sham group. In the first group, patients were treated by ESWT once a week for 4 weeks by a defined protocol. In the sham group, the same protocol was applied but with the probe being turned off. The follow-up assessments were done at 1, 2, 3, and 12 weeks by Visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 28 publications
(41 reference statements)
5
56
0
Order By: Relevance
“…Our initial search yielded 1611 potential citations from MEDLINE, Web of Science, EMBASE, and the Cochrane Library, of which 1605 were excluded for reasons presented in Figure S1. The literature search and study selection process, therefore, identified five RCTs in six publications that examined a total of 280 patients who were treated with Li‐ESWT (n = 140) or control (n = 140) for CP/CPPS from 2009 to 2018 . Of all the RCTs, three studies reported follow‐up data collected at 12 weeks after treatment and two presented 24‐week results .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our initial search yielded 1611 potential citations from MEDLINE, Web of Science, EMBASE, and the Cochrane Library, of which 1605 were excluded for reasons presented in Figure S1. The literature search and study selection process, therefore, identified five RCTs in six publications that examined a total of 280 patients who were treated with Li‐ESWT (n = 140) or control (n = 140) for CP/CPPS from 2009 to 2018 . Of all the RCTs, three studies reported follow‐up data collected at 12 weeks after treatment and two presented 24‐week results .…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows results of pain domain acquired from four trials . Of them, four reported them at the endpoint and 12 weeks, three at 4 weeks and two at 24 weeks. Similar to NIH‐CPSI total score, pain domain was significantly in favor of Li‐ESWT group at the endpoint (− 2.84 [− 4.73, − 0.95], P = 0.003), 4 (− 4.75 [− 7.29, − 2.21], P = 0.0002) and 12 weeks (− 5.60, [− 7.16, − 4.03], P < 0.00001) after the treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one study revealed different outcomes depending on how QoL was measured: while the QoL score of the NIH-CPSI increased with treatment, the SF-12 score remained unchanged on a low level [83]. Other treatment options, like psychotherapy [14,26], acupuncture [84][85][86][87], extracorporeal shock waves [88][89][90][91], osteopathy [92,93], electrical nerve stimulation [94], physical activity [55] or pollen extract [95], also showed a positive effect on QoL. In contrast, the injection of botulinum toxin A had a small effect on QoL [96] and sacral magnetic stimulation [97] was not shown to increase QoL.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Extracorporeal shock wave therapy frequently is used for the treatment of myofascial pain syndromes. Although many studies and reviews support the application of extracorporeal shock wave therapy 14,15,16,17 a recent RCT revealed contradictory results 18 . However for the application of extracorporeal shock wave therapy in patients with AIS we are looking for a mechanical effect.…”
Section: Introductionmentioning
confidence: 99%